Relationship between the Effect of Severity Vertigo and Demographic Characteristic for Iraqi Patients - Zainab Sabah Rashid; Ban Juma Abed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Vertigo, an illusory sensation of self or environmental rotation is a common presentation to the emergency department, affecting approximately 20–30% of the general population. Despite its frequency, most clinicians find acute vertigo challenging. An easy way of approaching it is to have in mind the most common causes and to consider them all during history taking and examination. Patients and Methods:A cross-sectional study involved 150 adult participants, who complained of vertigo and attended the vertigo center in Baghdad Medical City, using a 25-item Vertigo Handicap Questionnaire. During period (February – June) 2020. Results of Current study showed no effect of vertigo in (17.9%) of patients in age group (20-29) years. The effect of vertigo is more severe in female (3.3%) than in male (1.8%), so vertigo is more severe in patients with primary education (6.5%) and Mild effect of vertigo is more in retired patients (71.0%), while moderate effect of vertigo as (50.0%) in students and (35.0%) in governmental employed patients. As well as vertigo is more severe in patients live in rural area, Patients who have duration of symptom less than one year have no effect of vertigo in (3.8%), and severe effect in (3.8%), Also patients who currently employed (9.0%) had slight or no effect of vertigo. Conclusion: There is no significant correlation found between the severity of the effect of vertigo and demographic characteristic of studied individuals. The vertigo handicap questionnaire may be a useful tool for screening patients, counseling, and charting treatment progress.